Microwave-enhanced pyrolysis of biomass coupled with catalytic reforming for hydrogen production - Shi, Kaiqi (2015)
Pyrolysis of biomass is a promising and sustainable approach to produce value-added chemicals and biofuels. In order to achieve a high yield of hydrogen-rich syngas from pyrolysis of biomass, the microwave-enhanced pyrolysis of biomass coupled with catalytic reforming was studied systematically in this research. Firstly, microwave-enhanced pyrolysis of biomass was carried out and compared with conventional pyrolysis under the same processing conditions. Characterisations of biomass, pyrolytic char, bio-oil and biogas were conducted to investigate the differences between microwave-enhanced and conventional pyrolysis. It was found that certain types of carbon nano materials were formed on the surface of microwave pyrolytic chars. More biogas was produced via microwave heating, in which the highest H2 content reached 48.2vol.% during the course of microwave-enhanced pyrolysis of bamboo at 800°C. Most of the syngas contents produced from microwave-enhanced pyrolysis of biomass were above 80vol.% at 800°C. Generally, biomass could be converted into biofuel efficiently with microwave-enhanced process. Secondly, in order to increase hydrogen production, microwave-enhanced pyrolysis coupled with catalytic reforming (MPCCR) at 600°C was studied. In catalyst screening, Ni and Fe were applied as active compounds loaded onto different supports such as molecular sieves (13X), Al2O3 and natural minerals. In addition, activated carbon was employed as a reforming agent. It was found that Ni-13X catalyst resulted in a low yield of bio-oil and high yield of biogas around 75wt.%, which was the highest among all the catalysts investigated. It was also observed that activated carbon played a significant role in increasing biogas product and reducing bio-oil yield to less than 1wt.% in both conventional and microwave-enhanced pyrolysis coupled with reforming. MPCCR with Ni-13X and activated carbon enhanced cracking reactions of bio-oil, and subsequently lowed bio-oil yields and narrowed products distribution simultaneously. The maximum H2 content reached 55vol.% by MPCCR of bamboo using activated carbon as the reforming agent. Compared with conventional reforming, there was a sharp increase of H2 yield via microwave-enhanced reforming, resulting in a hydrogen-rich syngas with a high ratio of H2 to CO. Therefore, it is concluded that microwave irradiation enhances the reforming process. Finally, in this study, a novel method for catalyst-free synthesis of multi-walled carbon nanotubes (MWCNTs) from biomass was developed. MWCNTs with a diameter of 50 nm and a wall thickness around 5 nm have been successfully prepared via microwave-enhanced pyrolysis of gumwood at 500 °C. The mechanism for the growth of such carbon nanotubes (CNTs) was proposed as follows: volatiles were released from the biomass and left behind char particles; these char particles then acted as substrates, mineral matter in char particles (originating from biomass) acted as the catalyst, and the volatiles released act as the carbon source gas; the volatiles then underwent thermal and/or catalytic cracking on the surface of char to form amorphous carbon nanospheres; the carbon nanospheres subsequently self-assembled to form multi-walled CNTs under the effects of microwave irradiation. In summary, microwave-enhanced pyrolysis of biomass has the potential to produce high yield of hydrogen-rich syngas not only at high temperatures but also at low temperatures when it is coupled with catalytic reforming processes. It has also been demonstrated that microwave-enhanced pyrolysis of biomass could be used to produce MWCNTs at low temperatures. It can therefore be concluded that microwave-enhanced pyrolysis of biomass is an effective and efficient approach for the conversion of biomass into value-added products under mild conditions.